Effect of cover thickness on the yield of a solar distiller under the El oued climate, Algeria - Abderrahmane Khechekhouche; Mohammed El Hadi Attia; Ali Boukhari; Muthu Manokar; Zied Driss; Boubaker Benhaoua; Mokhtar Ghodbane (University of Eloued جامعة الوادي, 2019)
The wilaya of El Oued (southeastern Algeria) suffers from a huge lack of drinking water, unfortunately the groundwater is sometimes too salty for them considered drinking water. The most economical way to obtain drinking water is solar distillation using free, renewable and non-polluting energy. Improvement of the single-slope solar distiller is a problem addressed by several researchers around the world. This study also aims at this point by the variation of the thickness of the glass (the condenser). Experiments show that the production is better improved when the thickness of the glazing is low e = 3 mm with a total production of 2313.2 ml /m2.d; when e = 5 mm the production is 1876 ml / m2.d and at the end when e = 6 mm the production is 1236 ml / m2.d. From these results can be said that any increase in thickness will be followed by a decrease in the productivity of distilled water.
Keywords: Keywords—Desalination; distilled water; evaporation; condensation; Solar radiation